Electrons cross transfer in multislit electromagnetic trap “Jupiter 2M” - Lavrent’ev, O.A.; Maslov, V.A.; Germanova, S.V.; Nozdrachov, M.G.; Oboznyj, V.P.; Shevchuk, B.A.; Skoryk, N.A. (Вопросы атомной науки и техники, 2005)
The researches of cross electrons transfer in the central and face parts of a trap are carried out. It is shown, that increased electrons transfer in a face part is connected to presence here toroidal area of the superseded magnetic field. The change of a magnetic configuration has resulted in reduction of a cross electrons transfer in a face part, increase of density and negative potential of plasma.